Host-Derived Probiotics Shape the Intestinal Microbial Composition, but not Putative Function in Juvenile Japanese Seabass (Lateolabrax japonicus) - Yang, Hong-Ling; Liu, Zi-Yan; Jian, Jiu-Ting; Liu, Zi-Xin; Ye, Ji-Dan; Sun, Yun-Zhang (Frontiers in Marine Science, 2022)
A complex and dynamic microbiota exists in the intestine of fish and plays vital roles in host growth and health. However, the interactions between host originated beneficial bacteria/probiotics with gut microbiota are still largely unknown. The aim of the study is to investigate the impact of two host-derived probiotics, Lactococcus petauri LF3 and Bacillus siamensis LF4, on the intestinal microbiota of juvenile Japanese seabass (Lateolabrax japonicus). Fish were fed the control diet (C), L. petauri LF3 (LF3) and B. siamensis LF4 (LF4) supplemented diets for 6 weeks, and the intestinal microbial composition and function were evaluated by using high-throughput sequencing technology. The relative abundances of certain phyla changed significantly in the probiotic-supplemented groups, Fusobacteria and Proteobacteria decreased, while Firmicutes and Bacteroidetes increased apparently in the groups LF3 and LF4. The apparently increased relative abundances of intestinal possible beneficial Christensenellaceae_R-7_group and Lactobacillus were observed in the groups LF3 and LF4, especially in the group LF4. Compared with the control group (C), Chao1, Ace and Shannon indices enhanced remarkably in groups LF3 and LF4. Intestinal microbiota was determined to have more similarity and lower individual differences based on beta diversity analysis including PCoA, NMDS and UPGMA clustering tree in groups LF3 and LF4 compared with the control group (C). Additionally, Firmicutes as a significant biomarker emerged in the groups LF3 and LF4 compared with the control. The intestinal microbial functions (amino acid metabolism, carbohydrate metabolism, energy metabolism, membrane transport, etc.) did not alter among all groups based on level-2 KEGG pathways. In summary, host- derived probiotic L. petauri LF3 and B. siamensis LF4 shape the intestinal microbial composition, but not function in juvenile Japanese seabass (L. japonicus).